2003
DOI: 10.1108/02683940310502377
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hotel managers’ turnover cognitions

Abstract: This paper reports the findings of a study which tested a model that predicts the turnover cognitions of hotel managers. Several predictor variables of turnover intentions were identified: perceived psychological contract breach and felt violation; organisational commitment; career expectations; perceived managerial competencies; job satisfaction, career identity and career satisfaction; demographic and human capital characteristics; and organisational characteristics. A total of 14 hypotheses were tested. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 57 publications
(69 reference statements)
7
80
0
2
Order By: Relevance
“…Organizational commitment's role as a predictor of turnover intention also informed the work of Joo and Park (2009) which investigated aspects of job satisfaction, and learning and development in organizations. In a similar vein Fulford (2005) and Cho, Johanson, and Guchait (2009) propose a robust argument that organizational commitment is negatively related to turnover intention, while Gunlu et al (2010) are unequivocal in their argument that both affective and normative commitment have a significant effect on turnover intention (see also Carbery et al, 2003;Culpepper, 2011;Kuruüzüm et al, 2009;Labatmediene, Endriulaitiene, & Gustainiene, 2007;Nadiri & Tanova, 2010;Namasivayam & Zhao, 2007;Yang, 2010). On the basis of the above theoretical elements the following hypotheses are proposed:…”
Section: Organizational Commitment and Labor Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational commitment's role as a predictor of turnover intention also informed the work of Joo and Park (2009) which investigated aspects of job satisfaction, and learning and development in organizations. In a similar vein Fulford (2005) and Cho, Johanson, and Guchait (2009) propose a robust argument that organizational commitment is negatively related to turnover intention, while Gunlu et al (2010) are unequivocal in their argument that both affective and normative commitment have a significant effect on turnover intention (see also Carbery et al, 2003;Culpepper, 2011;Kuruüzüm et al, 2009;Labatmediene, Endriulaitiene, & Gustainiene, 2007;Nadiri & Tanova, 2010;Namasivayam & Zhao, 2007;Yang, 2010). On the basis of the above theoretical elements the following hypotheses are proposed:…”
Section: Organizational Commitment and Labor Turnovermentioning
confidence: 99%
“…Others have posited that low levels of job satisfaction, which is impacted by routinization, role conflict and lack of promotional opportunity (Carbery, Garavan, O'Brien, & McDonnell, 2003;Lambert, Lewig, & Dollard, 2003), can have deleterious effects on the organization. In the same vein, two further universal dimensions of the work experience, organizational commitment and job involvement, can impact not only an employee's decision to quit an organization, but also on its bottom line results (Deery, Iverson, & Walsh, 2002;Falkenburg & Schyns, 2007;Johnson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hallier and James 1997;Herriot, Manning and Kidd, 1997;Searle and Ball, 2004), the main focus of psychological contract research has been on the quantitative demonstration of how employees' perceptions of employer breaches of obligations lead to adjustments in employee attitudes and behaviours. For example, recent studies have demonstrated that psychological contract breach is negatively associated with job satisfaction (Tekleab et al, 2005), affective commitment (Coyle-Shapiro and Kessler, 2000), organizational citizenship behaviour (Johnson and O'Leary-Kelly, 2003), and inrole performance (Turnley and Feldman, 2000;Johnson and O'Leary Kelly, 2003) and positively related to turnover intentions (Lo and Aryee, 2003;Carbery, Garavan, O'Brien. and McDonnell, 2003;Lemire and Rouillard, 2005).…”
Section: Psychological Contract Research -Missing Employee Agencymentioning
confidence: 99%
“…High turnover is generally acknowledged as one of the distinguishing features of the hotel and hospitality industry [38]. Several studies have examined both the magnitude and costs of turnover in the hotel industry [39], [40].…”
Section: Turnovers In Hospitality Industrymentioning
confidence: 99%